English Indoensian Code Mixing Used by Sandiaga Uno s Speech in Youtube - Sukamto, Nurhalizha Puspa; Idayani, Andi (English Education Department, 2023)
It is commonly known that Indonesians speak their mother tongue along with the national language as well as foreign languages when interacting with one another in society The ethnic diversity cultural diversity and linguistic diversity of Indonesia help to create multilingual languages The purpose of this study was to determine the structure and purpose of the English Indonesian code mixing used by Sandiaga Uno in a speech video on YouTube This study used a descriptive qualitative method that was based on Creswell s theory and applied Sugiono s documentation based approach to data collection While the Miles and Huberman theory which included data reduction data display and conclusion verification is used for data analysis This study shows the many kinds and purposes of code mixing for each statement that Sandia Uno has uttered including code mixing of words phrases hybrids word reduplication idioms and clauses The study finds a few advantageous uses for code mixing in sandiaga uno They are: the motivation to experience need providing additional information and expressing one s emotions < p>